Mechanotribological Aspects of MXene-Reinforced Nanocomposites - Malaki, Massoud; Varma, Rajender S (Advanced materials (Deerfield Beach, Fla.), 2020)
MXenes are recently discovered 2D nanomaterial with superior mechanical, thermal, and tribological properties, being commonly employed in a wide variety of critical research areas, ranging from cancer therapy to energy and environmental applications. Due to their special properties, such as mechanoceramic nature with excellent mechanical performance, thermal stability and rich surface properties, MXenes have tremendous potential as advanced composite structures, especially those based on polymers due to a great affinity between macromolecules and the terminating groups of 2D MXenes. MXenes have been extensively explored in metal matrix nanocomposites as well as in solid- or liquid-based lubrication systems owing to the 2D structure and antifriction characteristics. The purpose of the this paper is to provide a comprehensive insight into the material, mechanical, and tribological properties of the MXene nanolayers with discussions on the recent advancements attained from MXene-reinforced nanocomposites starting with the synthesis, fabrication techniques, intricacies of the underlying physics and mechanisms, and finally focusing on the progress in computational studies. This analysis of MXene-based composites will stimulate an emerging field with innumerable opportunities and ample potentials to produce newfangled materials and structures with targeted properties.
Keywords: tribology; 2D materials; MXenes; composites; mechanical strength